Comparative photochemical and sonophotochemical performance of quinoline-substituted zinc and indium phthalocyanines for singlet oxygen generation - Karanlik, Ceren Can; Karanlik, Gurkan; Kocaaga, Nagihan; Boztepe, Halim; Erdogmus, Ali (PERGAMON-ELSEVIER SCIENCE LTD, 2026)
Sono-photodynamic therapy (SPDT), an innovative approach that uses light and ultrasound stimulants together, has been accepted as a more effective treatment method than photodynamic therapy (PDT) owing to its markedly enhanced treatment efficacy. Building on this, in the present article, zinc- and indium-metallated phthalocyanine (Pc) derivatives carrying 2-hydroxyquinoline segment at their peripheral positions have been synthesized. The molecular structures of the synthesized complexes have been clarified using 1H NMR, FT-IR and mass spectroscopic techniques. Photophysical, photochemical and sono-photochemical measurements were performed in order to reveal the singlet oxygen generation capacities of the Pcs for both photodynamic therapy (PDT) and sono-photodynamic therapy (SPDT) applications. The singlet oxygen quantum yield (Phi Delta) of the molecules was obtained as 0.49 for 2 and 0.86 for 3 upon photochemical measurements (utilizing only light irradiation), whereas these values increased to 0.75 for 2 and 1.29 for 3 upon sono-photochemical (utilizing light and ultrasound together) studies. The results demonstrate that the singlet oxygen production of a sensitizer is profoundly governed by stimulation modality, emphasizing the power of the synergistic effect of light and ultrasound in SPDT over PDT.
Keywords: Zinc phthalocyanine; Indium phthalocyanine; 2-hydroxyquinoline; PDT; SPDT; Singlet oxygen; IN-VITRO; THERAPY; MECHANISMS; Chemistry; Crystallography